Biologically-Based Complementary and Alternative Medicine (CAM) Use in Cancer Patients: The Good, the Bad, the Misunderstood - Knecht, Kathryn; Kinder, David; Stockert, Amy (Frontiers in Nutrition, 2020)
As complementary and alternative medicine (CAM) becomes more popular, it is being used in cancer patients to aid in recovery or to treat symptoms associated with the current chemotherapy. Numerous papers exist that discuss patients using CAM with cancer chemotherapy and their outcomes - both positive and negative. However, in the case of the negative outcomes, the reason for the dangers or interactions with drugs are not made clear. Indeed, many chemotherapy regimens are rendered less effective by the well-meaning but uninformed patient or their family members and friends. Similarly, reports of positive outcomes with CAM and chemotherapy provide a strong basis for further research, but do not identify specific mechanisms of action. These small clinical studies and in vitro studies identify a necessary area for further research and provide a much needed, although often rejected, alternative look at whole treatment plans. Careful review of the available information and evaluation of the nature of the CAM effects are necessary to combat the misunderstanding and sometimes unwarranted claims over CAM use. This mini review will explore some of the commonly used CAM agents and their mechanisms of interactions with other treatments. Suggestions as to which agents can be safe and when to use them will be an integral part of this review.